2016
DOI: 10.1103/physrevaccelbeams.19.011301
|View full text |Cite
|
Sign up to set email alerts
|

rf breakdown tests of mm-wave metallic accelerating structures

Abstract: We are exploring the physics and frequency-scaling of vacuum rf breakdowns at sub-THz frequencies. We present the experimental results of rf tests performed in metallic mm-wave accelerating structures. These experiments were carried out at the facility for advanced accelerator experimental tests (FACET) at the SLAC National Accelerator Laboratory. The rf fields were excited by the FACET ultrarelativistic electron beam. We compared the performances of metal structures made with copper and stainless steel. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 38 publications
0
51
0
1
Order By: Relevance
“…Recently, we have expanded our experiments on the basic physics of ultrahigh vacuum RF breakdown to the mm-wave range with beam-driven accelerators at FACET [13,14]. In this paper, we continue this study [15] using a 110 GHz MW pulsed gyrotron oscillator [16] as the RF power source.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have expanded our experiments on the basic physics of ultrahigh vacuum RF breakdown to the mm-wave range with beam-driven accelerators at FACET [13,14]. In this paper, we continue this study [15] using a 110 GHz MW pulsed gyrotron oscillator [16] as the RF power source.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments have shown that shorter exposure to high-field stresses reduces both the breakdown rate and the long-term material damage [2]. Therefore, power sources capable of delivering very high peak powers in very short pulses (such as nanoseconds for microwave frequencies, or femtoseconds for optical frequencies) have an advantage in producing very high gradients.…”
Section: Advanced Accelerator Conceptsmentioning
confidence: 99%
“…RF structures operating in the 100-200 GHz range offer the promise of high accelerating gradients and include features that are realizable with advanced standard machining techniques [7]. M. Dal Forno of SLAC National Accelerator Laboratory provided an overview of the mm-wave accelerating structure breakdown physics research program at SLAC, and presented results of quantitative measurements of rf breakdown rates in a 200 GHz structure driven by the intense electron beam at FACET.…”
Section: Millimeter-wave Accelerator Structuresmentioning
confidence: 99%
“…The experimental goal was to determine statistical properties of rf breakdown in these structures, including material tests for copper and copper-silver. The main diagnostics included arc detector to measure the field emission current and reliably detect rf breakdowns and a pyroelectric detector to measure the radiated energy [8]. The FACET beam parameters included 3.2 nC and varied bunch lengths.…”
Section: Millimeter-wave Accelerator Structuresmentioning
confidence: 99%